Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1365-2966.2012.21491.x
|View full text |Cite
|
Sign up to set email alerts
|

Two in one? A possible dual radio-emitting nucleus in the quasar SDSS J1425+3231

Abstract: The radio‐emitting quasar SDSS J1425+3231 (z = 0.478) was recently found to have double‐peaked narrow [O iii] optical emission lines. Based on the analysis of the optical spectrum, Peng et al. suggested that this object harbours a dual active galactic nucleus (AGN) system, with two supermassive black holes (SMBHs) separated on a kpc scale. SMBH pairs should be ubiquitous according to hierarchical galaxy formation scenarios in which the host galaxies and their central black holes grow together via interactions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 40 publications
(76 reference statements)
2
12
0
Order By: Relevance
“…Their peak efficiency is reached at a similar time after merger as in our simulations, but remains smaller than our peak value [Eq. (20)] by a factor of a few.…”
Section: Comparison With Previous Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their peak efficiency is reached at a similar time after merger as in our simulations, but remains smaller than our peak value [Eq. (20)] by a factor of a few.…”
Section: Comparison With Previous Resultsmentioning
confidence: 99%
“…A number of mechanisms may provide signals associated with these sources across a broad range of time scales from ∼10 9 years before merger to ∼10 9 years after merger [13]. Considerable evidence for binary SMBH systems has already been observed, but is restricted to those either well before merger [14][15][16][17][18][19][20][21], or well after merger [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…However, further observations of these candidate sources with high resolution found that only 1% of them could be genuine dual AGNs (Fu et al 2011a); in most of the sources this spectral behavior can be be explained by other effects not requiring dual AGNs (Heckman et al 1981(Heckman et al , 1984Xu & Komossa 2009;Crenshaw et al 2010). As shown by several works (e.g., Fischer et al 2011;Fu et al 2011a;Shen et al 2011;Tingay & Wayth 2011;Frey et al 2012;An et al 2013;Comerford et al 2013;Gabányi et al 2014;Kharb et al 2015;McGurk et al 2015), doublepeaked narrow lines alone are not good indicators to select compelling dual AGN candidates, other diagnostic methods have to be used. Comerford et al (2012) used high-resolution long-slit spectroscopy to select the most compelling dual AGN candidates from the double-peaked narrow emission line active galaxies.…”
Section: Discussionmentioning
confidence: 97%
“…The radio galaxy 4C37.11 contains a SMBH binary system with a 7.3 pc separation and ∼1.5 × 10 8 M in mass (Rodriguez et al 2006). In addition, there are several radio-bright DPEs in which double nuclei with separations of a few kpc are seen in high-resolution radio mapping, such as SDSS J1536+0441 (Wrobel & Laor 2009;Bondi & Pérez-Torres 2010), SDSS J1502+1115 (Fu et al 2011b), and SDSS J1425+3231 (Frey et al 2012). These results indicate that some DPE systems indeed host dual AGNs.…”
Section: Discussionmentioning
confidence: 78%